Studi Eksperimental Perbandingan Nilai Faktor Reduksi (Ï) Profil Baja Tabung Kotak di Indonesia - Nawir Rasidi (Journal of Mathematical and Fundamental Sciences, 2005)
At present, structural designing in Indonesia uses the value of reduction factor (Ï) according to LRFD-AISC regulation (Load and Resistance Factor Design â American Institute of Steel Construction). It is understood that different condition in Indonesia requires different approach, therefore this research attempted to determine a specific value of reduction factor (Ï).The research observes the compression and flexural behavior of profile steel boxes (2x4) cm with length 75 cm and 65 cm for compression and flexural test, respectively. This test collects resistance data that are stress, area of steel, load and modulus of elasticity. The result of flexural test with reliability index (Î²) = 3 obtained the value of reduction factor of flexure Ïb = 0.8823 and Ï = 0.5195 for compression test. Difference between this value and that of LRFD-AISC code were caused by nominal mean value-mean value ration, coefficient of variation (Î©), and the distribution used in the calculation. In addition, different reliability index of 2.5, 2, and 1.5 were also calculated for comparison. It is concluded that greater value of reduction factor (Ï) could be obtained with smaller reliability index (Î²).